2018
DOI: 10.1016/j.jviromet.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

A novel multiplex PCR for virus detection by melting curve analysis

Abstract: A B S T R A C TBackground: Rapid and accurate laboratory diagnoses of viral infections are crucial for the management and treatment of patients with viral infections. Conventional methods for virus detection are labourious, time consuming, and only a single virus can be analysed in one assay. Objectives: The objective of this study was to develop a novel real-time PCR method for multiple virus detection by melting curve analysis using Taqman probes in a single reaction. Study design: As a model, six respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
1
2
0
2
Order By: Relevance
“…This is similar to research of Chen et al [36] on Maillard reaction of soybean protein hydrolysates, that is, the sample after Maillard reaction has higher fluorescence intensity in the scope of 400-600 nm. A resembling phenomenon was also observed by Liu et al [37] that the fluorescence intensity enhanced with the growing time in the intermediate stage of the Maillard reaction in the fructose-histidine model system. Moreover, G-Cbcp displayed the highest fluorescence intensity, followed by G-Pbcp and G-Bbcp (P < 0.05).…”
Section: Fluorescence Intensitysupporting
confidence: 82%
“…This is similar to research of Chen et al [36] on Maillard reaction of soybean protein hydrolysates, that is, the sample after Maillard reaction has higher fluorescence intensity in the scope of 400-600 nm. A resembling phenomenon was also observed by Liu et al [37] that the fluorescence intensity enhanced with the growing time in the intermediate stage of the Maillard reaction in the fructose-histidine model system. Moreover, G-Cbcp displayed the highest fluorescence intensity, followed by G-Pbcp and G-Bbcp (P < 0.05).…”
Section: Fluorescence Intensitysupporting
confidence: 82%
“…The multiplex RT-PCR assays can help to save time and costs in testing for multiple viruses. Liu et al (2018) developed multiplex RT-PCR primers to successfully detect six respiratory viruses using TaqMan probes in a single reaction. Menzel et al (2002) found that the multiplex RT-PCR assays described are reliable, rapid, and sensitive methods to detect these viruses and may replace techniques that commonly require indexing by woody indicators or enzyme-linked immunosorbent assay.…”
Section: Discussionmentioning
confidence: 99%
“…They found that out of 307 patients, approximately 57% were infected by SARS-CoV-2 and at least one other influenza virus. Although non isothermal, PCR revolutionized the molecular biology field and biosensing applications because it is amenable to multiplexing, where more than one target can be amplified in a single reaction [ [327] , [328] , [329] , [330] , [331] ]. An RT-PCR-based multiplexed system was developed by US CDC named as “Flu SC2 Multiplex Assay” to codetect SARS-CoV-2 and influenza viruses [ 332 ].…”
Section: Isothermal Amplification Methods-based Detection: Scope and Challengesmentioning
confidence: 99%